Dental follicle mesenchymal stem cells regulate responses in sepsis - GÜL, FETHİ; CİNEL, İSMAİL HAKKI; ARSLANTAŞ, MUSTAFA KEMAL; AKKOÇ, TUNÇ (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: Sepsis-induced immune alterations are associated with secondary infections and increased risk of death. The use of mesenchymal stern cells (MSCs) has been described as a novel therapeutic strategy. We evaluated the immunomodulatory effects of human dental follicle (DF-MSCs) on lymphocytes of sepsis and septic shock patients. Materials and Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from venous blood samples of sepsis, septic shock and healthy subjects. PBMCs were co-cultured in the presence and absence of DF-MSCs with or without interferon-gamma (IFN-gamma) for 72 hours. CD4+CD25+FoxP3+regulatory T (Treg) cell frequency, lymphocyte proliferation, cytokine levels and apoptosis were evaluated via flow cytometry. Results: DF-MSCs significantly suppressed proliferation of lymphocytes in sepsis group compared to septic shock group (p<0.005). DP-MSCs remarkably increased Treg ratio in sepsis compared to control group (p<0.05). Reduction of lymphocyte apoptosis in cocultures of DF-MSCs and PBMC was significant in both sepsis and septic shock groups. IFN-gamma stimulation of DF-MSCs ameliorated shift in the T-cell subsets from Th2 to Th1 phenotype in septic shock. Conclusion: Our findings revealed that DEL MSCs have immunoregulatory effects both in sepsis and septic shock, by reducing interleukin-4 (IL-4) and increasing IFN-gamma levels. This immunoreactivity regulation may open new therapeutic approaches for septic shock patients.
Keywords: Sepsis; Septic shock; Dental follicle mesenchymal stem cells; Immunomodulation; HUMAN BONE-MARROW; INTERFERON-GAMMA; INDUCED IMMUNOSUPPRESSION; MECHANISMS; CYTOKINES